THE CHARACTERISTICS OF CONVEYOR BELT OF RUBBER COMPOUND BY USING COCONUT SHELL CHARCOAL AS THE FILLER - Dewantara Daud; Rahmaniar Rahmaniar (Jurnal Dinamika Penelitian Industri, 2017)
A research have been conducted about the characteristics of belt conveyor by using coconut shell charcoal filler material. The study aims to compare the physical properties of rubber compound for belt conveyor using coconut shell charcoal filler with carbon black filler material. The composition of rubber compound consist of natural rubber, polymer, mineral oils, TBBS, coconut shell charcoal and carbon black. Substitution of coconut shell charcoal to carbon black was done by varying the weight of coconut shell charcoal for 25 phr, 35 phr and 50 phr for comparison, data characteristic of belt conveyor rubber compound using carbon black type for ISAF, HAF, and FEF is used. The results showed the use of coconut shell charcoal as filler for belt conveyor compound has not been able to provide good physical properties such as carbon black. The highest physical properties of compound is obtained at the weight of coconut shell charcoal at 50 phr with the value of tensile strength (70 kg/cm2), elongation at break (320%), tear resistance (36 kg/cm2), hardness (62 shore A) and abrasion resistance (1.1 mm/kgm).